Preparation of nanocomposite cadmium sulfide in a polymer matrix - Goglidze, Tatiana (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
A technique for formation of CdS nanocrystals in a Sevilen polymeric matrix by the cluspol method is proposed. The optimum conditions of synthesis of CdS nanocrystals are found. The crystallite sizes are estimated using the X-ray diffraction analysis. The results of studying the luminescent properties of the resultant polymer nanodimensional CdS structures are described.